Ovary preservation in the treatment of childhood Meigs syndrome. Issue 11 (22nd May 2015) - Fremed, Michael A.; Levin, Terry L.; Sun, Katherine Y.; Weiser, Daniel A.
<x xml:space="preserve">Abstract</x> Meigs syndrome, the combination of benign ovarian tumor, ascites, and pleural effusion, is present in a small percentage of ovarian fibromas and is infrequently reported in children. When associated with elevated CA‐125 suspicion is raised for malignancy, often prompting aggressive surgical intervention. We present a case of childhood Meigs syndrome and review the relevant literature with emphasis on ovary preservation. Out of nine identified pediatric cases, one involved ovary sparing treatment and none recurred or progressed to malignancy. Our report highlights the importance of presurgical identification of Meigs syndrome in order to curtail salpingo‐oophorectomy when feasible. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.